Effect of clinic experience on pre-service professionals perceptions of applied special needs services. DOI: 10.5007/1980-0037.2011v13n2p145 - Chris Carpenter; Sean Cai (Universidade Federal de Santa Catarina, 2011)
With the understanding that the attitudes and expectations a teacher carries into the classroom directly affect student achievement, this study was administered to evaluate the cognitive affect that clinical experience incorporating individuals with disabilities had on pre-service exercise science professionals. University Students with and without experience in an adapted clinical environment were given surveys covering attitudes and perceptions towards classroom atmosphere, teachers' instructional techniques, inclusion, and self-efficacy. Data were analyzed and used to determine pedagogical implications. Findings suggest that pre-service educators tend to feel unprepared and ill-equipped to work in an inclusive educational environment. Therefore, pre-service teacher programs should ideally include coursework in adaptive education and experiential components such as practicum, field experience, and clinical experience. In addition, a school-university collaborative relationship can facilitate beneficial outcomes to future educators as well as special needs populations.